Menanamkan Nilai Akidah dan Ahklak di Era Digital - Gaffar, Abdul Gaffar (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
A person's character is greatly influenced by their religious education. However, teaching morals and religious values ​​is becoming increasingly difficult in the digital age. This article discusses how religious education can change over time to remain relevant and useful in developing the moral character of the next generation. This study emphasizes the value of creative teaching methods, the use of digital technology as a learning tool, and collaboration between communities, schools, and families in shaping students' character through a literature review and qualitative data analysis. A person's character is greatly influenced by their religious education. However, teaching morals and religious values ​​is becoming increasingly difficult in the digital age. The adaptability of religious teaching is examined in this article.